2011
DOI: 10.2478/v10183-011-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

Biology of generative reproduction of Colobanthus quitensis (Kunth) Bartl. from King George Island, South Shetland Islands

Abstract: Our macroscopic observations and microscopic studies conducted by means of a light microscope (LM) and transmission electron microscope (TEM) concerning the re− production biology of Colobanthus quitensis (Caryophyllaceae) growing in natural condi− tions in the Antarctic and in a greenhouse in Olsztyn (northern Poland) showed that this plant develops two types of bisexual flowers: opening, chasmogamous flowers and closed, cleistogamous ones. Cleistogamy was caused by a low temperature, high air humidity and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…Flowers and fruit are more abundant when weather conditions are more favorable, which happens every few years or even every ten or more years (Piro_ znikow 1993). Plant species native to the Antarctic produce numerous flowers and inflorescences nearly every year, but mature seeds do not emerge regularly on an annual basis (Convey 1996;Giełwanowska et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Flowers and fruit are more abundant when weather conditions are more favorable, which happens every few years or even every ten or more years (Piro_ znikow 1993). Plant species native to the Antarctic produce numerous flowers and inflorescences nearly every year, but mature seeds do not emerge regularly on an annual basis (Convey 1996;Giełwanowska et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Some grains do not leave the theca and germinate in microsporangia, whereas in most angiosperms, the theca opens when pollen grains reach the stage of a two-celled male gametophyte, and their generative cells divide into two sperm cells only during the growth of the pollen tube. The production of trinucleate gametophytes in closed microsporangia of Colobanthus quitensis was observed in our earlier study (Giełwanowska et al 2011). This strategy shortens the period between pollen release and successful fertilization, which minimizes the risk that pollen will be adversely influenced by external factors during its transport to the stigma.…”
Section: Morphology Of Generative Structures In Polar Caryophyllaceaementioning
confidence: 62%
“…-In this study, microscopic analyses revealed that Caryophyllaceae produced flower buds with (in most cases) normally developed microsporangia, microspores and male gametophytes. Selected attributes of microsporangia and male germ line cells in Antarctic phanerogams growing in their native habitats were discussed in our previous studies (Giełwanowska et al 2011).…”
Section: Morphology Of Generative Structures In Polar Caryophyllaceaementioning
confidence: 99%
“…-The results of microscopic analyses performed in this study indicate that both D. antarctica and P. annua produce flower buds with normally developed micro− sporangia, microspores and male gametophytes. The development of microspo− rangia and male germ line cells in polar plants growing in Antarctica was dis− cussed in our previous studies (Giełwanowska et al 2005(Giełwanowska et al , 2011. We observed that pollen grains of D. antarctica and P. annua reached the three−celled stage be− fore pollen discharge and that many grains did not leave the thecae and germinated inside microsporangia.…”
Section: Discussionmentioning
confidence: 82%